Politik Organisasi Pada Motivasi Karir Pegawai - Machin Machin; Khoiruddin Anas; Aslichah Aslichah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2023)
The aim of this research is to analyze the influence of organizational politics towards career motivation with the Career Motivation variable based on (London, 1989) and Based on the variable Perception of Organizational Politics (Ferris and Kacmar; 1996). The method used was a descriptive analysis method with a sample of 76 employeesusing Proportional Random Sampling and analyzed with a model AMOS structural equation. Research findings prove that there is a relationship which varies positively and significantly between organizational politics and Career Motivation political perceptions based on multi-dimensional career motivation in the career identity domain,and career insight domain